2016
DOI: 10.1111/dmcn.13180
|View full text |Cite
|
Sign up to set email alerts
|

Risk of stroke among patients with cerebral palsy: a population‐based cohort study

Abstract: LHIDLongitudinal Health Insurance Data AIM The aim of the study was to investigate the risk of stroke in patients with cerebral palsy (CP), based on nationwide data in Taiwan. RESULTS Patients with CP were more likely to suffer stroke than the comparison population, after adjusting for potential confounding factors (adjusted hazard ratio: 2.17; 95% confidence interval [CI]: 1.74-2.69). The hazard ratio of stroke was 4.78 (95% CI: 3.18-7.17) and 1.57 (95% CI: 1.20-2.05) for patients with CP aged 50 years and un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 32 publications
(60 reference statements)
0
40
0
1
Order By: Relevance
“…Of these, one only investigated the risk of stroke 118 and one was a cross-sectional study using self-reported presence of disease as the outcome. Only two studies so far have directly compared the risk of NCDs between adults with and without CP.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these, one only investigated the risk of stroke 118 and one was a cross-sectional study using self-reported presence of disease as the outcome. Only two studies so far have directly compared the risk of NCDs between adults with and without CP.…”
Section: Discussionmentioning
confidence: 99%
“…When directly compared with children having typical development, two out of three studies reported that a lower percentage of children with CP met guidelines 94,102,105. Burden of NCD among people with CP Seven studies reporting on the burden of NCDs among people with CP were identified(Table II): three crosssectional studies44,84,117 and four cohort studies [118][119][120][121]. Burden of NCD among people with CP Seven studies reporting on the burden of NCDs among people with CP were identified(Table II): three crosssectional studies44,84,117 and four cohort studies [118][119][120][121].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Exact cause of cerebral palsy is still unknown; however brain damage can occur before birth, during the birth and after the birth. Pregnancy disorders are considered leading cause before birth [4]. Birth asphyxia, prematurity, neonatal infections and traumatic brain injury are some important causes in cerebral palsy [5].…”
Section: Introductionmentioning
confidence: 99%